POLICY IMPLEMENTATION OF THE EQUALIZATION OF ADMINISTRATIVE POSITIONS INTO FUNCTIONAL POSITIONS - Rizki Amalia (Sosiohumaniora, 2023)
The Ministry of Administrative and Bureaucratic Reform has mandated all Ministries or Agencies to carry out independent position mapping assessments. In the Praja Extracurricular Program at the IPDN Jatinangor Campus, there are 2 (two) positions that have not received socialization in filling out the DUPAK. Time limitations in determining equivalent positions. Some employees resulting from equalization of positions experience difficulties in carrying out their main duties and functions. Have not paid attention to the match between the position name and the job description of a position at the meeting to determine the distribution of positions. Distribution of positions through the factors that influence it. This type of qualitative descriptive research. through factors that influence it in the Praja Extracurricular Section has been carried out quite well in the aspects of resources and dispositions, but there are still obstacles in the aspects of communication and bureaucratic structure.